21C 중국 대국화에 따른 한중 갈등요인 분석: 공세적 민족주의의 역할과 한계를 중심으로 - 오일환; Ilhwan Oh (중국연구, 2017)
Chinese neo-nationalism trend is formed of china traditional sino- centrism and offensive nationalism. The main reason of china's offensive foreign activity is from the china's confidence of turning into a strong nation. But this new trend of China's neo-nationalism might be interrupted in China-Korea relationship. This is an analysis of Chinese 21C new trend of nationalism and a prospect of nationalism interaction in sino-korean relation.